Modular prefabricated water storage tank for easy transport and quick assembly in remote areas - Kumar, Gopal; Sena, Dipaka; Sikka, Alok; Malaiappan, Sudharsan; Sammadar, A.; Madhu, M. (International Water Management Institute, 2025)
Water scarcity in hilly and remote regions persists despite moderate rainfall because of inadequate decentralized storage. The conventional masonry tanks are costly, slow to build, and unsuitable for rugged terrains. To address this, IWMI and ICAR under the CGIAR Multifunctional Landscapes Program developed a modular prefabricated water storage tank—a low-cost, flat-pack system that can be assembled within 20 minutes without tools or skilled labor. Made of galvanized-iron panels and a reinforced liner, the tank (≈11 kL) is portable, durable, and reusable, enabling rooftop rainwater harvesting, small-stream diversion, or solar-pump filling. Field demonstrations in Mandla, Madhya Pradesh, showed significant improvements in household water security, year-round vegetable production, and women’s time savings. The tanks also support agroecological homesteads, nurseries, and small-scale aquaculture. Affordable and scalable, the innovation aligns with CGIAR and IWMI priorities on climate-resilient water solutions, offering a replicable model for decentralized water storage and management across the Global South.